Pendampingan Pembelajaran Al-Qur’an bagi Anak dalam Mendukung Pendidikan Keagamaan di Kampung Cikoret, Desa Muaradua - Hikmatullah Hikmatullah; Muhammad Fauzan; Syaif Adiansyah; Shinta Robbi Marcharis; Nasuroh Nasuroh; Lisa Salimatus Sa’diyah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Religious education plays a vital role in shaping children's religious knowledge, skills, and habits from an early age. A key form of this education is Quranic learning specifically, the ability to read Iqra’ and the Quran correctly. However, given the varying reading abilities among children, guidance tailored to each child's proficiency level is essential. This community service initiative aims to describe the implementation of Quranic learning support for children in Kampung Cikoret, Muaradua Village, Cikulur District, Lebak Regency, Banten Province. Conducted as part of the Student Community Service (KKN) program, the initiative targeted 11 children who regularly attend Quranic study sessions during the Maghrib (sunset) period. A descriptive qualitative method was employed, utilizing data collection techniques such as observation, interviews, and documentation. The activity adopted an educational and participatory approach featuring direct, one-on-one instruction. The process included the practice of reciting daily prayers, shalawat (invocations of blessings upon the Prophet), and dhikr (remembrance of God) together; reading Iqra’ or the Quran according to each child's ability; and a closing prayer. The results indicate that individual guidance allowed children to receive specific instruction and corrections tailored to their respective proficiency levels. Furthermore, the practice of prayers, shalawat, and dhikr helped foster a religious learning atmosphere. This support also complemented existing Quranic education activities within the community. Thus, this Quranic learning support initiative serves as a contribution by KKN students toward facilitating the learning process and cultivating religious habits among children in Kampung Cikoret.